TÜRK MÜZİĞİNDE VİYOLONSELİN KULLANIMINA İLİŞKİN İCRACILARIN VE ÖĞRETİM ELEMANLARININ GÖRÜŞ VE YAKLAŞIMLARI. - AVCI AKBEL, Burcu (Electronic Turkish Studies, 2019)
This is a descriptive study which is aimed at revealing views of instructors and performers on the use of cello in Turkish Music both today and in the past, the performance style they adopt, the points of importance and criticism, and the suggestions regarding the learning process. Phenomenological methodology and maximum variation sampling were utilized in the research. Semi-structured interview method was used to collect data. The data obtained were analyzed by the content analysis method; NVivo12 software was used for the analysis. The study revealed that nowadays cello in Turkish Music is usually aimed for having a bass tone, or cello performers are expected to play the instrument for such kind of performance. Additionally, it was found out that the performance style is often acquired by listening to Turkish Music performers. It was also found out that the participants pay due attention to the criteria primarily including "knowledge of maqams, listening to the right sources, accurate finger pressures in Turkish Music, performance with adherence to the traditional style, being faithful to the original performance of a musical piece, technical exercises, transposing exercises, prominence of emotions, and ability to express emotion in performance"; and the participants also suggest that due attention should be paid to the mentioned criteria in the learning - teaching process. In terms of taksim performances, the participants suggested that performers should listen to and perform relevant pieces a lot, do ear training for adaptation to the related maqam, practice taksims by using semai and saz peşrev units, avoid impairing musical integrity when performing taksims, build correct connection between motifs, use phrases progressively and in question & answer concept, and produce melodies which make an emphasis on the geçkis within the musical piece to be performed after the taksim. It is anticipated that the criticisms, points of consideration and suggestions reported by the participants specialized in the field will be a beneficial guide for cello learners, instructors and academicians in field of Turkish Music.